Finding European bioethical literature: an evaluation of the leading abstracting and indexing services - Fangerau, H. (Journal of medical ethics, 2004)
Objectives: In this study the author aimed to provide information for researchers to help them with the selection of suitable databases for finding medical ethics literature. The quantity of medical ethical literature that is indexed in different existing electronic bibliographies was ascertained. Method: Using the international journal index Ulrich’s Periodicals Directory, journals on medical ethics were identified. The electronic bibliographies indexing these journals were analysed. In an additional analysis documentalists indexing bioethical literature were asked to name European journals on medical ethics. The bibliographies indexing these journals were examined. Results: Of 290 journals on medical ethics 173 were indexed in at least one bibliography. Current Contents showed the highest coverage with 66 (22.8%) journals indexed followed by MEDLINE (22.1%). By a combined search in the top ten bibliographies with the highest coverage, a maximum coverage of 45.2% of all journals could be reached. All the bibliographies showed a tendency to index more North American than European literature. This result was verified by the supplementary analysis of a sample of continental European journals. Here EMBASE covered the highest number of journals (20.6%) followed by the Russian Academy of Sciences Bibliographies (19.2%). Conclusion: A medical ethics literature search has to be carried out in several databases in order to reach an adequate collection of literature. The databases one wishes to combine should be carefully chosen. There seems to be a regional bias in the most popular databases, favouring North American periodicals compared with European literature on medical ethics.